HUBUNGAN PERAN KELUARGA DALAM FUNGSI SOSIALISASI DENGAN INTERAKSI SOSIAL REMAJA USIA PERTENGAHAN DI DUSUN LINGSAR KELING DIBAWAH WILAYAH KERJA PUSKESMAS LINGSAR LOMBOK BARAT - Sri Masdiningsih Utami; Ageng Abdi Putra; I Made Eka Santosa; Jihan Qirani (LPPM STIKES Mataram, 2025)
Adolescentsocialinteractionisdefinedastherelationshipandcommunicationthat occurs between adolescents and their peers. It includes emotional aspects and various shared social activities that play an important role in adolescents’ social and emotional development. Thisstudyaimstodetermineandanalyzetherelationshipbetweenthefamily'srole in the function of socialization and the social interaction of middle-aged adolescents in Dusun Lingsar Keling, under the working area of Lingsar Public Health Center, West Lombok Regency, in 2025. This research used a quantitative design with an analytical survey method and across-sectional approach .Atotal of 40 respondents were selecte dusing purposive sampling base don inclusion and exclusi oncriteria.The instrument sused were, questionnairesonthe family's role in the socialization function and the social interaction of middle-aged adolescents. TheresultsoftheSpearman'srhotestshowedthatthe numberofrespondentswas 40, with a significance value (2-tailed) of 0.000. Since the significance value is less than 0.05, it indicates a significant relationship between the family’s role in the function of socialization and adolescents’ social interaction. The correlation coefficient was 0.543, indicatingamoderateandpositiverelationship.Thesefindingsreinforcetheimportanceof the family’s role in shaping adolescents’social skills.